2019
DOI: 10.1177/0095244318819196
|View full text |Cite
|
Sign up to set email alerts
|

Tire tread rubber compounds with ternary system filler based on carbon black, silica, and metakaolin: Contribution of silica/metakaolin content on the final properties

Abstract: Carbon black and high performance silica have been widely employed as binary system filler in tire tread formulations. This study evaluated the total and partial substitution of silica by metakaolin (MK) on the properties of tread rubber composites. Dynamic mechanical thermal analysis and abrasion tests were conducted as typical assessments of tire tread performance: rolling resistance (fuel consumption), wet traction (safety), and abrasion (durability). Further the energy spent by the equipment during the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…5 MK (Figure 3), on the other hand, showed no significant difference between the experiments with and without silane, giving rise to two hypotheses: the first is that no reaction occurred between silane and MK and the second is that there was also agglomerate breakage, but the equipment was not sensitive enough to identify it. In our previous work, 11 we found that the Payne effect of MK is lower than that of silica, which means MK agglomerates have lower interaction energy, making them more brittle.…”
Section: Resultsmentioning
confidence: 79%
See 3 more Smart Citations
“…5 MK (Figure 3), on the other hand, showed no significant difference between the experiments with and without silane, giving rise to two hypotheses: the first is that no reaction occurred between silane and MK and the second is that there was also agglomerate breakage, but the equipment was not sensitive enough to identify it. In our previous work, 11 we found that the Payne effect of MK is lower than that of silica, which means MK agglomerates have lower interaction energy, making them more brittle.…”
Section: Resultsmentioning
confidence: 79%
“…where μ is the crosslink density, V r is the volume fraction of rubber in the swollen sample (equation (5)), V 0 is the molar volume of the solvent (106.29 mL mol −1 for toluene), and χ is the Flory–Huggins interaction parameter between the solvent and the elastomer (0.405 11 ):…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The larger the tan δ value is, the better the wet skid resistance. The tan δ at 60 • C is used to characterize the rolling resistance of the composite [28,29]. The higher the tanδ value is, the higher the rolling resistance.…”
Section: Dynamic Thermo-mechanical Analysismentioning
confidence: 99%